Plant densities and harvesting times on productive and physiological aspects of Stevia rebaudiana Bertoni grown in southern Brazil - GOMES,ERIK N. (2018)
Abstract Stevia (stevia rebaudiana Bertoni) is a species characterized by producing non-caloric substances with high sweetening potential. Among these substances, rebaudioside A and stevioside are produced in greater quantity. Plant density and harvesting time are factors that affects biomass and sweetening compounds yield in this species. The objective of this research was to evaluate the effect of plant densities and harvesting times on the productive and physiological characteristics of stevia in southern Brazil. The experimental design was in randomized blocks, in a split-plot scheme, with 9 treatments comparing the effect of three planting densities (166 667, 83 333 and 33 333 plants ha-1) in the plots and three harvesting periods (before, in the beginning and in full flowering) in the subplots. Harvesting at the beginning of flowering promoted higher dry leaf biomass yield and, when associated with the lowest planting density, promoted higher levels of rebaudioside A and stevioside. The lowest planting density resulted in greater leaves biomass accumulation, whereas the highest density promoted higher yields per area. Interaction between density of 166 667 plants ha-1 and the harvest at the onset of flowering promoted higher yields of rebaudioside A (43.22 kg ha-1) as well as higher rebaudioside A/stevioside ratio (0.60).